Pd3P nanoparticles decorated P-doped graphene for high hydrogen storage capacity and stable hydrogen adsorption-desorption performance. (August 2022) - Jin, Chaonan; Li, Jiao; Zhang, Keyan; Habibullah,; Xia, Guanghui; Wu, Chaoling; Wang, Yao; Cen, Wanglai; Chen, Yiwen; Yan, Yigang; Chen, Yungui
Abstract: The emergence of graphene provides a new research vector for the development of hydrogen storage materials. Herein, we firstly report a Pd3 P nanoparticles decorated P-doped graphene material by a facile pyrolysis method for hydrogen storage. The size of Pd3 P particles is distributed on the graphene surface uniformly in the range of 20–30 nm. It has a high gravimetric density of hydrogen storage of 3.66 wt% at mild conditions (298 K, 4 MPa). When the temperature drops to 253 K, the hydrogen storage capacity increases to 3.94 wt%; whereas at the pressure of 5.5 MPa and 298 K, the hydrogen storage capacity is up to 4.7 wt%. The Pd3 P nanoparticles decorated P-doped graphene has both physical and chemical hydrogen adsorption mechanisms during the hydrogen storage process. The hydride produced by chemical adsorption remains stable even at 498 K, which is the main reason for 1.03 wt% of the capacity loss during the hydrogen adsorption-desorption cycle. After 4 cycles of hydrogen adsorption-desorption at 298 K and 4 MPa, the effective hydrogen storage capacity of Pd3 P nanoparticles decorated P-doped graphene is 2.63 wt%, and the Pd3 P nanoparticles on the graphene are evenly distributed with stable structure after cycles, which is conducive to the realization of reversible hydrogen storage. Graphical Abstract: ga1 Highlights: Firstly synthesized 20 nm Pd3 P nanoparticles modified P-doped rGO for H2 storage. The Pd3 P/P-rGO stores as high as 4.7 wt% H2 at 298 K and 5.5 MPa H2 . The H2 desorption capacity is 3.55 wt%, 75.5% of total H2 adsorption capacity. The Pd3 P/P-rGO shows extraordinary cycle stability at room temperature.